Study on the correlation between age and changes in mosquito bite response - Oka, Keiko; Ohtaki, Noriko; Igawa, Ken; Yokozeki, Hiroo (Journal of dermatology, 2018)
Mosquito bite reactions consist of an immediate response characterized by an erythema and a wheal, which peaks at 20 min, and a delayed response characterized by a papule and/or an erythema, which peaks at 24 h. Mosquito bite reactions progress from stage I to stage V as an individual is repeatedly bitten as follows: stage I, neither immediate nor delayed reaction; stage II, delayed reaction; stage III, both immediate and delayed reaction; stage IV, immediate reaction; and stage V, neither immediate nor delayed reaction. In 1985, we conducted a cross‐sectional study that demonstrated a positive association between age and stage in response to an Aedes albopictus bite among 162 healthy volunteers. However, it remains unknown how the mosquito bite reaction stage progresses in the same individual over decades. In the present study, the mosquito bite reaction of 10 subjects from the 1985 cross‐sectional cohort was longitudinally evaluated over 30 years. We confirmed the time‐dependent progression of stage in four subjects. One stage II subject and three stage III subjects had advanced to the next stage. We went on to find that, contrasting with the general trend found in the previous studies, the majority of the subjects (6/10) remained of stage III over the 30‐year study period. Upon closer inspection, this apparently non‐progressive group demonstrated a reduction in the size of the delayed reactions. The present study demonstrated a marked individual variability in course of the stage progression.